ASSESSMENT OF EATING BEHAVIOR AND FOOD NEOPHOBIA IN CHILDREN AND ADOLESCENTS FROM UBERABA-MG - Taísa Alves Silva; Maísa Tirintan Jordani; Isabela Garcia da Cunha Guimarães; Luciene Alves; Camila Bitu Moreno Braga; Sylvana de Araujo Barros Luz (Sociedade de Pediatria de São Paulo, 2020)
ABSTRACT Objective: To investigate and compare the eating behavior and food neophobia of children and adolescents from different age groups, body mass index per age, and sex. Methods: This was a cross-sectional study, with a convenience sample, involving 150 children and adolescents aged 3 to 13 years, of both sexes, treated at a pediatric outpatient clinic of a teaching hospital in the municipality of Uberaba-MG, Brazil. Subscales of the Child Eating Behavior Questionnaire (CEBQ) were used to evaluate eating behavior, and the Child Food Neophobia Scale (CFNS) was used to evaluate food neophobia. Results: Higher scores were found in the subscales "food responsiveness" (p=0.015), "enjoyment of food" (p=0.002), and "emotional overeating" (p=0.009) among older children and adolescents. Younger children had higher scores in the subscales "satiety responsiveness" (p=0.004) and "slowness in eating" (p=0.001). There was a tendency toward higher scores for "food responsiveness" (p=0.005) and "emotional overeating" (p=0.013) in participants with severe obesity. There were no differences in the scale of food neophobia. Overall, food neophobia positively correlated with lack of interest in food and negatively correlated with interest in food. Conclusions: The study showed significant differences in some domains of eating behavior among children and adolescents of the sample; however, no differences were found regarding food neophobia. These results may contribute to the improvement of future interventions related to infant eating behavior and food neophobia.